2009
DOI: 10.1002/smll.200900466
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles of Diameter 1.4 nm Trigger Necrosis by Oxidative Stress and Mitochondrial Damage

Abstract: Gold nanoparticles (AuNPs) are generally considered nontoxic, similar to bulk gold, which is inert and biocompatible. AuNPs of diameter 1.4 nm capped with triphenylphosphine monosulfonate (TPPMS), Au1.4MS, are much more cytotoxic than 15-nm nanoparticles (Au15MS) of similar chemical composition. Here, major cell-death pathways are studied and it is determined that the cytotoxicity is caused by oxidative stress. Indicators of oxidative stress, reactive oxygen species (ROS), mitochondrial potential and integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
514
3
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 705 publications
(549 citation statements)
references
References 37 publications
(38 reference statements)
26
514
3
6
Order By: Relevance
“…[35] Equally important seems to be their size, for example, 1.4 nm gold nanospheres resulted in necrosis, damage to mitochondria and induction of oxidative stress, while 15 nm gold nanospheres did not harm the cells. [32] Many authors focused on the impact of physical and chemical parameters, such as particle size, shape or charge, while the effect of a degree of nanoparticle purification on the biological model was not tested. Today, many preparations of gold sols are available in commercial sales, but they are not equipped with information on the degree of purification from the residues after synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Equally important seems to be their size, for example, 1.4 nm gold nanospheres resulted in necrosis, damage to mitochondria and induction of oxidative stress, while 15 nm gold nanospheres did not harm the cells. [32] Many authors focused on the impact of physical and chemical parameters, such as particle size, shape or charge, while the effect of a degree of nanoparticle purification on the biological model was not tested. Today, many preparations of gold sols are available in commercial sales, but they are not equipped with information on the degree of purification from the residues after synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have revealed CNTs disrupt the membrane potential, membrane integrity, metabolic activity and cellular reproduction [137,138]. Gold nanoparticles are responsible for mitochondrial damage, affecting cellular micro mobility, autophagy and oxidative stress [119,139]. In vitro studies on silver nanoparticles' toxicity have suggested that interference with DNA replication, fidelity, apoptosis, oxidative stress, cytotoxicity, chromosome instability, intracellular calcium transients, JNK activation and cell cycle arrest in mammalian cells [121-125, 140, 141].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…The binding of such functional molecules to the surface of AuNPs is facilitated via thiol groups, resulting in a relatively stable gold-sulfur bond. Established cytotoxicity tests including gene expression studies have proved those AuNPs to be nontoxic (7)(8)(9). In contrast, ultrasmall AuNPs (sub-2 nm) may become cytotoxic, when the capping ligands are weaker binding phosphines instead of thiols.…”
mentioning
confidence: 99%
“…This cytotoxicity was size dependent in several cell lines and most severe in the case of AuNPs comprising a 55-gold-atom cluster core with a diameter of 1.4 nm and a shell consisting of 12 TPPMS molecules (Au1.4MS) (10). Toxicity was caused by oxidative stress (8). We further showed that cytotoxicity (i) was abolished by replacing the phosphine ligands by thiols, which bind more strongly to the gold core, and (ii) decreases with increasing particle size with a significantly reduced toxicity already at 1.8 nm.…”
mentioning
confidence: 99%